Changes in oxygen uptake kinetics after exercise caused by differences in loading pattern and exercise intensity. (25th March 2020) - Ichikawa, Yuri; Maeda, Tomoko; Takahashi, Tetsuya; Ashikaga, Kohei; Tanaka, Shiori; Sumi, Yuki; Itoh, Haruki
Abstract: Aims: The kinetics of recovery‐period oxygen uptake (VO2 ) are affected by the O2 deficit generated during exercise. However, studies using ramp tests (RTs) and constant work rate tests (CT) have differently characterized VO2 responses to increased exercise intensity differently. We used these two types of loading patterns to investigate the effects of low‐ intensity, medium‐ intensity, and high‐ intensity exercises on the half time (T1/2 ) of recovery‐period VO2 and the mechanism. Methods and results: Ten healthy men aged 21.2 ± 0.9 years underwent symptom‐limited cardiopulmonary exercise tests with the ramp protocol to determine their anaerobic threshold. All subjects subsequently underwent three submaximal RT and CT at low, moderate, and high intensities. In all RTs, subjects began exercise by warming up (20 W). In CT, T1/2 was significantly lengthened as exercise intensity increased (CT‐low: 34.0 ± 3.9 s, CT‐moderate: 39.5 ± 3.5 s, CT‐high:44.6 ± 4.2 s; P  < 0.01, ANOVA), whereas no significant change was observed in RT, which began with the same work rate (RT‐low: 46.0 ± 5.7 s, RT‐moderate: 45.7 ± 4.8 s, RT‐high: 44.6 ± 3.5 s, RT‐max: 44.8 ± 3.2 s; P  = 0.868, ANOVA). Only high‐intensity exercise resulted in two components (the fast and slow components) of VO2 decay, reflecting the increased O2 deficit by anaerobic metabolism. Conclusions: The exercise intensity at the beginning of an exercise affects early recovery‐period VO2, which is a fast component. The T1/2 of recovery‐period VO2 occurs during the fast component, and an increase in O2 deficit affects both the fast and slow components, lengthening the T1/2 . The T1/2 of recovery‐period VO2 in CT at moderate or high intensities, even if not symptom limited, can be used to evaluate exercise intolerance and early occurrence of anaerobic metabolism. Submaximal exercise tests may be considered as convenient methods for evaluating exercise tolerance in patients with cardiac failure.